Study of a new interlocking stabilised compressed earth masonry block - Eires, R. (2012)
Earth has been a traditional construction material to build houses in Africa. One of the most common earthen masonry techniques is the use of sun dried or kiln fired adobe bricks with mud mortar. Although this technique is cheap and allows the self construction, the bricks vary largely in shape, strength and durability. This has lead historically to weak houses which suffer considerable damage during floods and seismic events. Furthermore, the use of firewood kilns to burn bricks has caused extensive deforestation in several countries of Africa. A solution which has been proposed in the second half of the last century is the use of stabilised compressed earth blocks (CEBs). These blocks are manufactured by compacting stabilised earth in a manual or hydraulic press. The resulting blocks present higher values of strength and durability, as well as uniform shapes. Since earth is available almost in every location of the world, the CEBs can be produced in-situ. The fact that this blocks are unburned and that the transport can be omitted makes them a cheap material with very low embodied energy. Their use is a cost effective opportunity for locals to have better houses while reducing deforestation. In this context one developed an ongoing study for the manufacture of CEBs according to different materials available in Malawi. It is envisaged that the constructive solution with theproposed CEBs will enable improvements in durability, in thermal and acoustic comfort and in seismic behaviour of buildings in Malawi, where earth is an abundant material and labour isunskilled. This paper presents some results of the experimental campaign which has been carried out. Forthis purpose, soils from Malawi were characterized and tested without stabilization, as well aswith cement and/or lime addition.